Pengaruh Green Marketing dan Green Consumerism Terhadap Keputusan Pembelian Produk Ramah Lingkungan - Evilia Nur Fadilah (Pusat Riset dan Inovasi Nasional, 2024)
The issue of plastic waste in Indonesia has reached alarming levels with annual production reaching 64 million tons, the majority of which ends up in the oceans, making Indonesia the second largest contributor to global marine plastic pollution after China. Increasing awareness and reducing daily waste generation are crucial to protecting the environment from the serious impacts of plastic's slow decomposition. This research employed accidental sampling with 20 to 30 respondents to investigate the influence of green marketing and green consumerism on purchasing decisions of environmentally friendly products. Data analysis included data exploration to identify patterns and trends, and Ordinary Least Squares (OLS) regression testing to evaluate the linear relationship between independent variables (green marketing and green consumerism) and the dependent variable (purchase decision). The results of multiple linear regression analysis indicate that the Green Consumerism variable (X2) has a positive regression coefficient of 0.260, although it is not statistically significant (p = 0.148), suggesting that consumer adoption of environmentally friendly behavior marginally contributes to purchasing decisions of environmentally friendly products. However, the low Adjusted R Square (0.031) indicates that the model only explains approximately 3.1% of the variability in purchase decisions. Therefore, companies need to consider other factors such as price and product quality, and integrate more holistic marketing strategies to enhance consumer preference for environmentally friendly products. Further research using more sensitive analytical methods could provide deeper insights to support more effective decision-making in dynamic markets.